2016
DOI: 10.1016/j.apcata.2016.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-free semihydrogenation of acetylene alcohols in a capillary reactor coated with a Pd–Bi/TiO 2 catalyst

Abstract: A solvent-free semihydrogenation of 2-methyl-3-butyn-2-ol (MBY) to 2-methyl-3-buten-2-ol was performed in a capillary reactor (10 m long, 0.53 mm i.d.) coated with a titania supported Pd-Bi catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 84 publications
3
32
0
Order By: Relevance
“…In our previous works, we have demonstrated that the catalyst-coated tube reactors are very efficient in providing high selectivity towards intermediate hydrogenation products over the Bipoisoned Pd catalysts [28,36]. The selectivity in such reactors was demonstrated to be as high as in an ideal batch reactor with the same catalyst.…”
Section: Characterisationmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous works, we have demonstrated that the catalyst-coated tube reactors are very efficient in providing high selectivity towards intermediate hydrogenation products over the Bipoisoned Pd catalysts [28,36]. The selectivity in such reactors was demonstrated to be as high as in an ideal batch reactor with the same catalyst.…”
Section: Characterisationmentioning
confidence: 99%
“…Hence, the maximum product selectivity obtained is determined only by the catalyst chemistry with no handicap being brought by the reactor [24,28]. However, the catalyst-coated tubes were demonstrated so far only at the milligram [38] to 10 g a day throughput levels [28,36], which are not suitable for industrial applications [35,39,40]. We have extrapolated the experimental performance of the tube reactors wall-coated with the Pd/ZnO catalyst and showed that a throughput of above 4 kg a day is feasible in a single 5 m long 1.5 mm ID reactor in the solvent-free MBY semihydrogenation [41].…”
Section: Characterisationmentioning
confidence: 99%
See 3 more Smart Citations